Is this a good place to live? A queer narrative hermeneutics of geographies, homes, and bodies ... - Maine, Emilie Mariah (Graduate Studies, 2023)
This dissertation asks a phenomenological question about the experiences of queer-identifying people, applying a narrative hermeneutic approach to interpret those experiences. This dissertation asks: How do queer people experience what it is like to live in Fort McMurray, Alberta in their homes and in their bodies? Through an embodied epistemology, narrative hermeneutic methodology, and queer theory, this dissertation queries into if Fort McMurray is a good place to live for queer people. Data collected from three collective interviews, and one final individual interview with three participants, provided new knowledge and understandings into how queer people in the northern Canadian urban service area of Fort McMurray learn to work and live in and across three nested systems – geography, home, and body. ...